Quality changes in Chinese high-quality indica rice under different storage temperatures with varying initial moisture contents - Zhu, Dongyi; Wang, Tingting; Liu, Xiuying; Bi, Jie; Zhang, Wei; Zeng, Xuefeng; Wang, Pingping; Shu, Zaixi (Frontiers in Nutrition, 2024)
The planting area of high-quality indica rice varieties has been growing rapidly in China. However, the storage characteristics of these varieties remains unclear. In this research, different moisture contents (13.5%, 14.5%, and 15.5%) of high-quality rice (variety Xiadao No.1) were stored at different temperatures (15, 20, 25, and 30 ºC) for 360 d, and then evaluated for lipid metabolism, redox enzyme activities, fatty acid composition, and sensory attributes. With the prolongation of storage, rice displayed an upward trend in fatty acid value, malondialdehyde content, and cooked rice hardness and a downward trend in contents of total fat and non-starch lipid, peroxidase and catalase activities, and sensory score of cooked rice. The change trends of these quality parameters were aggravated by elevating storage temperature and moisture content. Linoleic acid content of rice generally decreased with prolonged storage. After 300 d of storage, rice with initial moisture content of 13.5% at 30 ºC showed a fatty acid value of higher than 30 mg KOH/100 g, while rice of other two initial moisture contents reached similar level at 25 ºC. After the whole storage period, only rice with initial moisture contents of 13.5% and 14.5% stored at 15 ºC had a sensory score of higher than 60. These results suggested that the aging process of high-quality rice can be inhibited by decreasing the storage temperature and initial moisture content. These results can provide reference for grain storage enterprises to select proper storage condition to store high-quality rice.